Seropositivity of Helicobacter Pylori among the Fish Handlers - Ullah, SS; Shamsuzzaman, SM; Ara, MN; Islam, MN; Islam, MS; Saha, M; Tahmina, S; Nag, D; Lutfor, AB (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):219-24. The abstract of this article is available on the PubMed website